Constantine’s City: the Early Days of a Christian Capital - Berger, Albrecht (Studia Ceranea, 2021)
In his new city Constantinople, Constantine the Great established an imperial cult with pagan elements prevailing over Christian ones. This can be seen from a number of monuments and buildings, such as the Forum of Constantine with the emperor’s statue on a column, the Capitol, the emperor’s mausoleum, the Mesomphalon, and the temple of the city goddess Tyche.